Diderot et la colonisation. À propos du « Supplément au Voyage de Bougainville » - Brix, Michel (Verbum – Analecta Neolatina, 2010)
In the Supplément au Voyage de Bougainville (‘Supplement to Bougainville’s Voyage’), Diderot develops the idea of the problem of travelling and colonizing, which the scholars misunderstood. The main point does not focus on the conflict, or the competition, between two civilization patterns — the so-called "primitivism" of Tahiti and the advanced society of Europe. Regarding the anti-colonialist impact, Supplément goes far beyond a simple stand: Diderot indeed anticipates the disastrous consequences (of which we are very aware today) of the travels made by Europeans to the more distant regions of the world from the 15th century.